Гідрогеологічні аспекти газоносності верхньобаденських відкладів Зовнішньої зони Передкарпатського прогину - Гарасимчук, В.; Лук’янчук, Д. (Геологія і геохімія горючих копалин, 2010)
На основі досліджень палео- та сучасних гідрогеологічних умов верхньобаденського горизонту Зовнішньої зони Передкарпатського прогину розкрито основні закономірності формування і збереження його газових покладів.
Виявлено, що газові поклади пов’язані з усіма генетичними типами вод, поширеними на цій території. У межах локальних полів поклади тяжіють до ділянок
з підвищеною мінералізацією вод та ознаками інтенсивних постседиментогенних
процесів.
На основі гідробаричних даних встановлено приуроченість більшості газових
покладів до ділянок як регіональних, так і локальних баромінімумів. З ділянками
баромаксимумів часто пов’язані поперечні тектонічні порушення. Взаємозв’язок
баромаксимумів з підвищеними значеннями мінералізації вод визначає тектонічні
порушення як шляхи міграції флюїдів. On the basis of paleohydrogeological and modern hydrogeological features of Upper
Badenian Aquifer the main condition of the formation and preservation of the hydrocarbon pools are determined.
Working out was based on the factual material on ion-salt composition of waters of
the Upper Badenian horizon (165 samples) and formational pressures (66 measurements)
obtained from the funds of Zakhidukrgeologia State Enterprise. The present-day plane
hydrogeochemical zonality of the Upper Badenian horizon of the Outer Zone of the Carpathian Foredeep was worked out in a form of diagrammatic maps of mineralization, a
gradient of mineralization, genetic coefficients rNa/rCl, rSO₄ • 100/rCl, Cl/Br.
To determine hydrodynamic characteristic of the Upper Badenian horizon we have
used the methods of formation pressures reduced to one absolute mark and taking the allowance for density of waters into consideration. Hydrobaric zonality is represented by the
diagrammatic map of formation pressures consolidated to the absolute mark of 500 m.
Upper Badenian Aquifer of the north-western and central parts of the Outer Zone is
formed by sedimentary waters of the Late Badenian sea. Presence of low mineralized
waters is caused by infiltration from the East-European Platform. Upper Badenian Aquifer
of the underlying part contains the pressing out brines from the Sambir-Rozhnyativ cover.
Among these types of water their mixtures are present.
Regional hydrochemical features of the Upper Badenian Aquifer of the Outer Zone
of the Carpathian Foredeep indicate the space connection of the gas pools with all these
genetic types of waters. Within the local hydrogeochemical fields the gas pools gravitate
towards the areas with high mineralization and features of the intensive postsedimentogenous processes.
Most of gas pools are confined both to regional and local hydrobarominima areas.
The transverse tectonic ruptures are connected with the areas of hydrobaromaxima and
high mineralization. These features point out the tectonic ruptures as the ways of fluid
migration. Saving of gas deposits within discovered hydrodynamic systems is a result of
the availability of hydrodynamic screens.